2023
DOI: 10.1186/s13045-023-01452-2
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal circRNA: emerging insights into cancer progression and clinical application potential

Abstract: Exosomal circRNA serves a novel genetic information molecule, facilitating communication between tumor cells and microenvironmental cells, such as immune cells, fibroblasts, and other components, thereby regulating critical aspects of cancer progression including immune escape, tumor angiogenesis, metabolism, drug resistance, proliferation and metastasis. Interestingly, microenvironment cells have new findings in influencing tumor progression and immune escape mediated by the release of exosomal circRNA. Given… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(21 citation statements)
references
References 190 publications
0
21
0
Order By: Relevance
“…One of the important functions of cirRNAs is to bind with RNA or proteins to regulate alternative splicing and transcription ( Wang H. et al, 2019 ; Xu Y. et al, 2020 ). Dysregulated circRNAs and their contribution to influencing various malignancies have been well researched, with potential for clinical applications ( Li et al, 2015 ; Zhang et al, 2023 ). Exosome-encapsulated circRNAs are found to be more stable in the serum/plasma of patients and, hence, more likely to indicate accurate lncRNA-associated clinical insights than other free circRNA species ( Li et al, 2015 ).…”
Section: Exosomes and Exosome-derived Biomoleculesmentioning
confidence: 99%
“…One of the important functions of cirRNAs is to bind with RNA or proteins to regulate alternative splicing and transcription ( Wang H. et al, 2019 ; Xu Y. et al, 2020 ). Dysregulated circRNAs and their contribution to influencing various malignancies have been well researched, with potential for clinical applications ( Li et al, 2015 ; Zhang et al, 2023 ). Exosome-encapsulated circRNAs are found to be more stable in the serum/plasma of patients and, hence, more likely to indicate accurate lncRNA-associated clinical insights than other free circRNA species ( Li et al, 2015 ).…”
Section: Exosomes and Exosome-derived Biomoleculesmentioning
confidence: 99%
“…Exosomes can promote tumor growth and metastasis by modulating the microenvironment and promoting angiogenesis, invasion, and immune evasion 45 . Exosomes secreted by cancer cells can also transfer oncogenic factors, such as miRNAs and proteins, to adjacent or distant cells, thereby promoting or inhibiting cancer development and resistance to therapy 46 In the early stages of cancer, cancer cell‐derived exosomes can induce apoptosis of neighboring cells, thereby promoting tumor development. However, in the later stages of cancer, cancer cell‐derived exosomes can inhibit the apoptosis of cancer cells, thereby promoting tumor survival and resistance to therapy 47…”
Section: Exosomes In Different Types Of Pcdmentioning
confidence: 99%
“…Exosomal circRNAs have a significant role in gastrointestinal cancers, as research has revealed in recent years ( 133 , 134 ). It has been demonstrated that circRNA has an impact on the proliferation, metastasis, stemness, angiogenesis, immune microenvironment and drug resistance of gastrointestinal tumors, and may develop into a useful therapeutic target for gastrointestinal malignancies as well as a potential biomarker ( 135 ). Although more studies have focused on the application of exosome-derived circRNAs in gastrointestinal tumors, there are still a number of problems to be solved.…”
Section: Challenges and Perspectivesmentioning
confidence: 99%